Optimization of VQE-UCC Algorithm Based on Spin State Symmetry - Guo, Qing; Chen, Ping-Xing (Frontiers in Physics, 2021)
The accurate calculation of molecular energy spectra, a very complicated work, is of importance in many applied fields. Relying on the VQE-UCC algorithm, it is very possible to calculate the molecular energy spectrum on a noisy intermediate scale quantum computer. However, due to the limitation of the number of qubits and coherent time in quantum computers, the complexity of VQE-UCC algorithm still needs to be reduced in the simulation of macromolecules. We develop a new VQE-UCC method to calculate the ground state of the molecule according to the symmetry of the system, the complexity of which is reduced. Using this method we get the ground and excite state of four kinds of molecules. The method and the results are of great significance for the promotion of quantum chemical simulations.